Identification and transcriptome data analysis of ARF family genes in five Orchidaceae species - Bai, Y.; Ma, Y.; Chang, Y.; Zhang, W.; Deng, Y.; Zhang, N.; Hu, T.
The Orchidaceae is a large family of perennial herbs especially noted for the exceptional diversity of specialized flowers. Elucidating the genetic regulation of flowering and seed development of orchids is an important research goal with potential utility in orchid breeding programs. Auxin Response Factor (ARF)genes encode auxin-responsive transcription factors, which are involved in the regulation of diverse morphogenetic processes, including flowering and seed development. However, limited information on the ARF gene family in the Orchidaceae is available. In this study, 112 ARF genes were identified in the genomes of 5 orchid species (Apostasia shenzhenica, Dendrobium catenatum, Phalaenopsis aphrodite, Phalaenopsis equestris and Vanilla planifolia,). These genes were grouped into 7 subfamilies based on their phylogenetic relationships. Compared with the ARF family in model plants, such as Arabidopsis thaliana and Oryza sativa, one group of ARF genes involved in pollen wall synthesis has been lost during evolution of the Orchidaceae. This loss corresponds with absence of the exine in the pollinia. Through mining of the published genomic and transcriptomic data for the 5 orchid species: the ARF genes of subfamily 4 may play an important role in flower formation and plant growth, whereas those of subfamily 3 are potentially involved in pollen wall development. the study results provide novel insights into the genetic regulation of unique morphogenetic phenomena of orchids, which lay a foundation for further analysis of the regulatory mechanisms and functions of sexual reproduction-related genes in orchids.
Keywords: ARF; AUXIN RESPONSE FACTOR; GENOME-WIDE IDENTIFICATION; ORCHIDACEAE; TRANSCRIPTOME